Study on Cold End Temperature Optimization of Supercritical CO2 Cycle - Kaiyun ZHENG (发电技术)
Supercritical CO2 cycle has a high cold end temperature. Optimizing the cold end temperature plays an important role in improving the cycle efficiency. In order to obtain the best annual average efficiency, it is necessary to introduce artificial refrigeration to make the supercritical CO2 cycle run at a more optimized cold end temperature. For the supercritical CO2 recompression cycle with parameters of 550℃/20MPa, the annual average cycle efficiency under different cold end temperature of 5 to 35℃, with the combination of natural cooling and artificial refrigeration was analyzed by thermodynamic method, and the feasibility and economic analysis of the cold end temperature optimization method were studied as well. The annual average efficiency of the unit can be improved by choosing the optimal cold end temperature and combining natural cooling with artificial refrigeration. For northern China, the cold end temperature optimization method has better feasibility. The artificial refrigeration increases the investment of unit equipment, but the improvement of operation efficiency brings more power generation revenue and moreover increases the net income of the unit during its life cycle.